2003
DOI: 10.1097/01.brs.0000092372.73527.ba
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Antidepressants in the Treatment of Chronic Low Back Pain

Abstract: Based on a small number of studies, tricyclic and tetracyclic antidepressants appear to produce moderate symptom reductions for patients with chronic low back pain. This benefit appears to be independent of depression status. SSRIs do not appear to be beneficial for patients with chronic low back pain. There is conflicting evidence whether antidepressants improve functional status of patients with chronic low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
13

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(101 citation statements)
references
References 27 publications
2
86
0
13
Order By: Relevance
“…Most of these reviews were published [6,42,76,78,83,88,90,135,146,190,192], but preliminary results from one Cochrane review on patient education (A. Engers et al, submitted for publication) that has been submitted for publication were also used. Because no Cochrane review was available, we used two recently published systematic reviews for the evidence summary on antidepressants [161,170]. The Cochrane review on work conditioning, work hardening, and functional restoration [163] was not taken into account because all trials included in this review were also included in the reviews on exercise therapy and multidisciplinary treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these reviews were published [6,42,76,78,83,88,90,135,146,190,192], but preliminary results from one Cochrane review on patient education (A. Engers et al, submitted for publication) that has been submitted for publication were also used. Because no Cochrane review was available, we used two recently published systematic reviews for the evidence summary on antidepressants [161,170]. The Cochrane review on work conditioning, work hardening, and functional restoration [163] was not taken into account because all trials included in this review were also included in the reviews on exercise therapy and multidisciplinary treatment.…”
Section: Methodsmentioning
confidence: 99%
“…There are three reasons for using antidepressants in the treatment of LBP [170]. The first reason is that chronic LBP patients often also cope with depression, and treatment with antidepressants may elevate mood and increase pain tolerance.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Two separate reviews of available literature found evidence for pain relief with antidepressants, but no significant impact on functioning [70,71].…”
Section: Antidepressantsmentioning
confidence: 99%
“…28,63,130 The relationship between depression and pain is reinforced by the fact that antidepressant drugs have an analgesic effect in musculoskeletal pain patients even without depression. 108 Even if the relationship between chronic pain and depression has been widely studied in other musculoskeletal conditions, very few studies analyze this relationship in AKP patients. Carlsson 13 used the Rorschach test in a group of patients with AKP comparing it to a control group.…”
Section: Relationship Between Depression and Anterior Knee Painmentioning
confidence: 99%